Elevated hypertension risk for African-origin populations in biracial societies: Modeling the Epidemiologic Transition Study. Issue 3 (March 2015) - Cooper, Richard S.; Forrester, Terrence E.; Plange-Rhule, Jacob; Bovet, Pascal; Lambert, Estelle V.; Dugas, Lara R.; Cargill, Kathryn E.; Durazo-Arvizu, Ramon A.; Shoham, David A.; Tong, Liping; Cao, Guichan; Luke, Amy
Abstract : Objectives: Blood pressures in persons of African descent exceed those of other racial/ethnic groups in the United States. Whether this trait is attributable to the genetic factors in African-origin populations, or a result of inadequately measured environmental exposures, such as racial discrimination, is not known. To study this question, we conducted a multisite comparative study of communities in the African diaspora, drawn from metropolitan Chicago, Kingston, Jamaica, rural Ghana, Cape Town, South Africa, and the Seychelles. Methods: At each site, 500 participants between the age of 25 and 49 years, with approximately equal sex balance, were enrolled for a longitudinal study of energy expenditure and weight gain. In this study, we describe the patterns of blood pressure and hypertension observed at baseline among the sites. Results: Mean SBP and DBP were very similar in the United States and South Africa in both men and women, although among women, the prevalence of hypertension was higher in the United States (24 vs. 17%, respectively). After adjustment for multiple covariates, relative to participants in the United States, SBP was significantly higher among the South Africans by 9.7 mmHg ( P  < 0.05) and significantly lower for each of the other sites: for example, Jamaica: −7.9 mmHg ( P  = 0.06), Ghana: −12.8 mmHg ( P  < 0.01) and Seychelles: −11.1 mmHg ( P  = 0.01). Conclusion: These data are consistent with prior findings of a blood pressure gradient in societies of the African diaspora and confirm that African-origin populations with lower social status in multiracial societies, such as the United States and South Africa, experience more hypertension than anticipated based on anthropometric and measurable socioeconomic risk factors.